Do ultrasound guided trochanteric bursa injections of corticosteroid for greater trochanteric pain syndrome provide sustained benefit and are imaging features associated with treatment response?. Issue 5 (May 2018) - Bolton, W.S.; Kidanu, D.; Dube, B.; Grainger, A.J.; Rowbotham, E.; Robinson, P.
Abstract : Aim: To assess intra-bursal corticosteroid injections (ICSI) efficacy and duration of action in the management of greater trochanteric pain syndrome (GTPS). The secondary aim was to identify patient and ultrasound (US) features predictive of treatment response. Materials and methods: Consecutive prospectively recruited patients undergoing US-guided ICSI therapy for GTPS received baseline pre-injection questionnaires assessing pain at rest and activity, demographics and comorbidities. Baseline US and radiography findings were reported prospectively. Follow-up was performed at 6 weeks and 6 and 12 months, and change in pain scores assessed using the Wilcoxon signed rank test. Logistic regression examined associations between demographics, US findings, and a clinically significant reduction in pain score (≥50%). Results: Over 6 months, 127 patients were recruited with a median age of 63.5 years and 90% were female. The greatest pain reduction was between baseline and 6 weeks at activity (median 8 versus 5, p< 0.001). The majority of patients noted a reduction in pain score, but the percentage of patients receiving a ≥50% reduction at 6 weeks, 6 months, and 12 months for pain at rest was 41%, 37%, and 36%, respectively. Regression models suggested only gluteus medius bursitis was weakly associated with pain reduction. Conclusion: ICSIs confer a benefit in pain reduction to a large proportion of patients in the short term, but this may not be reduced by a clinically significant amount. This small effect size and lack of predictive imaging features suggests initial management including subsequent steroid injection could be provided without imaging guidance in the majority of cases. Highlights: Greater trochanteric pain syndrome (GTPS) is a complex, common condition. Intra-bursal corticosteroid injections can reduce pain symptoms for GTPS patients. These benefits are short lived (6 months) and may not be clinically significant. Ultrasound does not provide imaging features predictive of treatment response.